QOS ANALYSIS OF LEO SATELLITE BROADBAND NETWORK FOR IOT IN SMART FARMING - Ramadhani, Eka Hero; Enriko, I Ketut Agung; Sari, Erika Lety Istikhomah Puspita; Alamsyah, Ahmad Tossin; Nuha, Muhammad Azza Ulin (STKIP PGRI Tulungagung, 2025)
The need for food in the form of agricultural products is currently increasing along with the growth of the world's population. However, the workforce in the agricultural sector in the modern era is decreasing because many young people are reluctant to become farmers. Therefore, the concept of Smart Farming emerged to overcome this problem by helping farmers manage and run agriculture efficiently using modern technology that can work automatically or be monitored or operated remotely using the internet network, for example, the Internet of Things (IoT) Smart Farming. However, agricultural areas located in remote or isolated villages are difficult to reach by terrestrial internet network infrastructure. Therefore, Low Earth Orbit (LEO) satellite broadband network infrastructure can be a new solution, so it needs to be researched. This research analyzes the Quality of Service (QoS) of LEO satellite broadband networks in IoT Smart Farming. The methods used consist of prototyping, experimentation, and analysis. QoS analysis based on throughput, packet loss, delay, and jitter parameters. The results of the experiment and analysis of this study indicate that the throughput value is 1243 bps. The speed test results show an average download speed of 88,89 Mbps and an upload speed of 14,08 Mbps. The packet loss value is 0%, which means that all packets were successfully sent. The average delay value is 97 ms. The jitter value is 26 ms. The results of this study can be further studied and developed for other use cases that are constrained by terrestrial internet network infrastructure.